Dental Pulp Stem Cells Model Early Life and Imprinted DNA Methylation Patterns. (19th January 2017) - Dunaway, Keith; Goorha, Sarita; Matelski, Lauren; Urraca, Nora; Lein, Pamela J.; Korf, Ian; Reiter, Lawrence T.; LaSalle, Janine M.
Abstract : Early embryonic stages of pluripotency are modeled for epigenomic studies primarily with human embryonic stem cells (ESC) or induced pluripotent stem cells (iPSCs). For analysis of DNA methylation however, ESCs and iPSCs do not accurately reflect the DNA methylation levels found in preimplantation embryos. Whole genome bisulfite sequencing (WGBS) approaches have revealed the presence of large partially methylated domains (PMDs) covering 30%-40% of the genome in oocytes, preimplantation embryos, and placenta. In contrast, ESCs and iPSCs show abnormally high levels of DNA methylation compared to inner cell mass (ICM) or placenta. Here we show that dental pulp stem cells (DPSCs), derived from baby teeth and cultured in serum-containing media, have PMDs and mimic the ICM and placental methylome more closely than iPSCs and ESCs. By principal component analysis, DPSC methylation patterns were more similar to two other neural stem cell types of human derivation (EPI-NCSC and LUHMES) and placenta than were iPSCs, ESCs or other human cell lines (SH-SY5Y, B lymphoblast, IMR90). To test the suitability of DPSCs in modeling epigenetic differences associated with disease, we compared methylation patterns of DPSCs derived from children with chromosome 15q11.2-q13.3 maternal duplication (Dup15q) to controls. Differential methylation region (DMR) analyses revealed the expected Dup15q hypermethylation at the imprinting control region, as well as hypomethylation over SNORD116, and novel DMRs over 147 genes, including several autism candidate genes. Together these data suggest that DPSCs are a useful model for epigenomic and functional studies of human neurodevelopmental disorders.